Visions from abroad historical and contemporary representations of Arabia - Khazindar, Mona 1959- (Skira, 2019)
Arabia was certainly the most mysterious country in the world during the historical era, an impenetrable and unknowable realm capable of stimulating the imagination and indeed the wildest fancies of the European intellectual elite. While the Hejaz region, where the two holy cities of Islamic Mecca and Medina are located, is still simply off-limits to non-Moslems, the rest of this vast land was at least as inaccessible and dangerous with its terrible deserts populated by Bedouins, whose reputation was enough to discourage the most fearless traveller. A small handful did, however, risk their lives to journey through Arabia and return with the rare texts and images that form the subject of this publication. These works, or rather the most captivating and successful of them in historical, anthropological and aesthetic terms, are gathered together in 'Visions from Abroad. Historical and Contemporary Representations of Arabia' and presented in a dozen thematic chapters. The book constitutes the first world view of Arabia as seen by authors and artists with the common characteristic of being born outside the peninsula. Drawing on both European and Arab sources, it presents images as well as the writings of historians and geographers, such as Ibn Battuta from the Maghreb and the no less renowned Ibn Jubayr from Andalusia, as well as travellers' accounts of pilgrimages
Unten auf der Titelseite neben dem Verlagslogo: "ithra" (i.e. King Abdulaziz Center for World Culture (Ithra), Dhahran, Saudi Arabien)
Keywords: Geschichte; Rezeption; Arabien -- Motiv; Kunst; Europa; Arabien; Arabian Peninsula / Description and travel; Arabian Peninsula / Description and travel / Pictorial works; Travel; Arabian Peninsula; Pictorial works